Vibrio fluvialis: An Emerging Pathogen for Intestinal and Extraintestinal Infections - Quazi Manjurul Haque; Md Arifur Rahman; Abdullah Akhtar Ahmed; Md Zulfikar Ali (KYAMC Journal, 2023)
The genus Vibrio is a ubiquitous group of bacteria belonging in the family Vibrionaceae. More than 100 species have been discovered in the genus Vibrio and about 14 of them have been reported to cause several human infections. Vibrio fluvialis, a member of this group is widely distributed in the aquatic environment, mostly in the seas, brackish waters and coastal zones.1 V. fluvialis is a pathogenic bacterium more commonly found in coastal areas. It causes diarrhea and enterocolitis and a significant number of extra intestinal infections. Due to increasing number of infections, it is considered as an emerging pathogen.1 Though this pathogen can be easily isolated by conventional staining and culture methods along with the biochemical properties, its identification is considered as a challenging problem due to its close phenotypic similarity of this species either with other vibrios and Aeromonas spp. By using automated BD Phoenix M50 techniques, it has become easier to identify V. fluvialis from clinical and different environmental samples. In this system biochemical properties of different 45 substrates are used to observe their fermentation reactions. Automated identification and antimicrobial susceptibility test systems are essential for modern clinical microbiology laboratories for rapid identification and proper selection of effective antibiotics. Several virulence factors of V. fluvialis have been identified.2 The rule and mechanisms of action of these virulent factors causing pathogenesis and infection are yet to be clarified. In this review article, the epidemiology, identification, pathogenicity, intra- and extra-intestinal clinical features and management of V. fluvialis infections have been focused. KYAMC Journal Vol. 14, No. 01, April 2023: 48-53